Relações de gênero em livros didáticos de Língua portuguesa dos anos finais do ensino fundamental da rede pública de ensino - Bastos, Maria Cristina Caamarotti da Silva (2015)
This study investigated gender relations that are conveyed in textbooks of Portuguese Language, the final years of elementary school, adopted under the National Textbook Program - PNLD, based on the book entitled "Português Linguagens", adopted by the School Our Lady of Fatima for the triennium 2014-2016, the author William Roberto Cereja and Thereza Cochar Magalhães strand Magellan author published in 2012 by Editora Saraiva. The determination of this investigative process was the need to understand the role of language in identity issues of gender and as the men's in the texts of textbooks contribute to the perpetuation of a patriarchal model of culture where men and women do not receive equal treatment in the various spheres of society. Its main analytical category gender, the work was done from the analysis of texts, the dialogue of the author / reader and reading of images (drawings and photographs) present in the adopted book. An analysis of how gender is represented in the content of textbooks was conducted for evidence of the presence of stereotypes, discrimination and sexist culture contained in the text and which the interference of this theme in the training / education of pupils and students. To meet our work, we opted for methodological literature, documentary research and content analysis emphasizing the thematic analysis. Is a discussion of "gender" in the classroom, emphasizing how gender relations circulated in the textbook and the entire configuration brought by it: text, images and relationship author / receiver, contribute to the perpetuation of stereotypes placed by the macho culture. We found that the school as a privileged educational space to make cultural changes, does not appropriate this context, by contrast, has a tendency to maintain and consolidate stereotyped patterns in the configuration and representation of men and women in sexist perspective. The textbook, recognized as the largest collection of historically accumulated knowledge, in our study did not show any evidence of being change of vehicle of gender relations, oppositely, turned out to be an instrument of consolidation and permanence of the macho culture. We interpret the situation found due to low speed of contemporary education to reflect and redesign new educational practices that redirect the role of people in your group, in your community, based on equal rights.